Peningkatan Kapasitas Pengrajin Bambu desa Banjarwaru dalam Bidang Pemasaran dan Jaringan - Ari Kristiningsih; Khoerudin Wittriansyah; Hety Dwi Hastuti; Theresia Evila PSR; Jenal Sodikin; Nurlinda Ayu Triwuri; Ilma Fadlilah (Karunia: Jurnal Hasil Pengabdian Masyarakat Indonesia, 2023)
Banjarwaru Village known as bamboo crafts village. Originally it was just a household product, it began to develop into a product that has aesthetic value. Sales of handicraft products are also starting to grow, they are starting to spread to other areas. Then the problem arises, namely inconsistent sales levels. To overcome this problem, the Cilacap State Polytechnic carried out Community Service activities by conducting Focus Group Discussion (FGD) activities by inviting resource persons from business actors to discuss with Banjarwaru village craftsmen. The aim of this activity is that Banjarwaru village craftsmen can find solutions to increase the level of sales of their craft products. From the results of the FGD, it was found that steps that can be taken to increase sales levels are carrying out business legality, building networks with the government, consumers, and fellow business actors, and increasing promotions through digital platforms.